Citizen and Independent Journalism in the Syrian War: Intersections Between Activism and Professionalism - Teixeira, Gisela Cardoso (2024)
The present article analyzes the journalistic coverage of the Syrian civil war, one of the deadliest armed conflicts in recent decades, by local citizen and independent journalists. It aims to explore how these actors report on the events of the war, considering their motivations in journalism and their processes of selecting themes and news sources. To address the research question, semi-structured interviews were conducted with 18 Syrian journalists, and the results were analyzed using a mixed methodology that combines discourse and content analysis. The findings show that citizen and independent journalists focus on themes related to the suffering and resilience of the population, using sources considered credible due to their direct experience on the ground. This type of journalism is characterized by a denunciatory and mobilizing discourse, reflecting a sense of justice and a connection to the community. Furthermore, it is observed that the subjectivity of these journalists, influenced by their personal experiences and convictions, distinguishes their narratives from traditional journalism.